2016
DOI: 10.1159/000449170
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Dopamine Receptor 1A and Cannabinoid Receptor 1 Genes in the Cochlea and Brain after Salicylate-Induced Tinnitus

Abstract: The purpose of this study was to investigate the mRNA expression of the dopamine receptor 1A (DR1A) and cannabinoid receptor 1 (CR1) genes in mice with tinnitus. Sixteen 3-month-old male SAMP8 mice were randomly and equally divided into two groups (8 mice in each group): a control (saline-treated) group and a tinnitus (salicylate-treated) group. The mRNA expression of the DR1A and CR1 genes in the cochleae and brains of the mice was evaluated after tinnitus had been induced by intraperitoneal injection of sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…Previous studies have reported that CB2 receptors are expressed in HEI/OC1 cells 29 and in the albino rat cochlea 32 . Another study found CB1 expression in SAMP8 mice cochleae 33 . We sought to determine whether cannabinoid receptors (CB1 and CB2) are expressed in UB/OC1 cells and in the rat cochlea.…”
Section: Resultsmentioning
confidence: 96%
“…Previous studies have reported that CB2 receptors are expressed in HEI/OC1 cells 29 and in the albino rat cochlea 32 . Another study found CB1 expression in SAMP8 mice cochleae 33 . We sought to determine whether cannabinoid receptors (CB1 and CB2) are expressed in UB/OC1 cells and in the rat cochlea.…”
Section: Resultsmentioning
confidence: 96%
“…GRK6 is a G protein-coupled receptor kinase that modulates dopamine receptors, and overexpression has been noted to attenuate neuropathic pain and rescue levodopa-induced signaling abnormalities. [49][50][51] Dopamine antagonists have shown promise in attenuating tinnitus. 52 Interestingly, MFHAS1 and XKR6 are associated with neuroticism.…”
Section: Discussionmentioning
confidence: 99%
“…For example, gene expression and/or function of N-methyl D-aspartate (NMDA) receptor (NR) increased in the inner ear and/or auditory nervous system 2,3 . On the contrary, function and/or gene expression of the γ-amino butyric acid (GABA) receptor (GR) and cannabinoid receptor in some brain areas decreased in the condition of tinnitus [4][5][6] . In addition, oxidative stress damage and/or neural inflammation in the peripheral and central auditory system were also important mechanisms of tinnitus [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%